Born global digital startups response to the impact of Artificial Intelligence - Zunaid, Abdullah (My University, 2025)
This study investigates the strategic role of Artificial Intelligence in enhancing digital marketing effectiveness and driving internationalization performance and business success in born-global digital startups. In today’s rapidly evolving global business landscape, these firms face mounting pressure to scale operations quickly and competitively, often under resource constraints. Digital technologies, particularly AI, offer a transformative avenue for these firms to streamline operations, personalize marketing efforts, and respond more agilely to international market demands. Despite growing academic and practitioner interest, limited empirical research has systematically examined the impact of AI adoption on the marketing, international expansion outcomes and ultimate business success of digitally born-global ventures. Addressing this gap, the study adopts the Resource-Based View as its theoretical foundation, conceptualizing AI as a strategic, intangible asset that contributes to sustained competitive advantage. A quantitative, cross-sectional research design was employed, involving a structured survey distributed to 70 digitally active startups engaged in international business activities. The data were analyzed using correlation, regression, and moderation analysis to assess the relationships among key constructs, including AI adoption in BGDS, digital marketing strategies, business performance, and internationalization success. The results reveal statistically significant and positive relationships between AI adoption in BGDS and digital marketing strategy, with strong effects on international performance. Specifically, the findings suggest that AI enhances firms' ability to engage in customer-centric, data-driven marketing, leading to improved market reach and performance in global contexts. Moreover, the study uncovers the moderating effects of resource availability and firm size on the relationships between AI adoption and internationalization outcomes. These findings underscore that while AI adoption can serve as a strategic enabler, its benefits are contingent upon certain enabling conditions—such as organizational readiness and resource capacity. This highlights the nuanced interplay between technological capability and structural support in achieving international growth. The study contributes to the growing body of literature on technology-driven internationalization by offering empirical validation of AI’s role in shaping marketing innovation and global competitiveness in the startup context. Additionally, it provides actionable insights for digital entrepreneurs, marketing strategists, and policymakers seeking to foster AI readiness and integration among internationally oriented startups. Although the research is limited by its sample size and cross-sectional nature, it lays the groundwork for future longitudinal studies and theory development in the areas of AI-enabled capabilities and digital globalization.
Keywords: internationalisation; artificial intelligence; marketing; enterprises; international market; strategies; corporate strategies; startup companies; international cooperation; digital marketing; marketing research; marketing communication; business operations; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business